Basidiomycota Macrofungal Communities Across Four Altitudinal Ranges in Bukit Baka Bukit Raya National Park, Indonesia - Harun, Natasya Adelia; Lovadi, Irwan; Rahmawati, Rahmawati; Joharudin, Didin (Universitas Gadjah Mada, 2024)
The influence of elevation gradient has been investigated across different taxa. However, such studies are scarce for macrofungal communities. This study examined the community structure of Basidiomycota macrofungi across four elevations in Bukit Baka Bukit Raya National Park, Indonesia. Macrofungi were collected from randomly placed five 10 x 10 m plots at each altitude and identified at the genus level. The results showed that there were 32 genera belonging to 20 families. The NMDS ordination and ANOSIM confirmed that macrofungal composition and abundance do not differ between the studied altitudinal ranges.